Polarimetric survey of main-belt asteroids: IV New results from the first epoch of the CASLEO survey - Gil Hutton, Ricardo Alfredo (2014)
Aims: We present results of a polarimetric survey of main-belt asteroids at Complejo Astronómico El Leoncito (CASLEO), San Juan, Argentina. The aims of this survey are to increase the database of asteroid polarimetry, to estimate diversity in polarimetric properties of asteroids that belong to different taxonomic classes, and to search for objects that exhibit anomalous polarimetric properties. Methods: The data were obtained using the Torino and CASPROF polarimeters at the 2.15 m telescope. The Torino polarimeter is an instrument that allows simultaneous measurement of polarization in five different bands, and the CASPROF polarimeter is a two-hole aperture polarimeter with rapid modulation. Results: The survey began in 1995, and until 2012 data on a large sample of asteroids were obtained. We here present and analyze the unpublished results for 129 asteroids of different taxonomic types, 56 which were polarimetrically observed for the first time. We find that the asteroids (402) Chloe and (729) Watsonia are Barbarians, and asteroid (269) Justitia shows a phase – polarization curve that seems to have a small inversion angle. Data obtained in UBVRI colors allow us to sketch an analysis of the wavelength dependence of the degree of linear polarization for 31 asteroids, in spite of some large error bars in some cases.